Spatial Planning Judgments and Computer Supported Collaborative Planning. (1st January 2019) - Milz, Dan
ABSTRACT: The role of planning support systems has become closely aligned with the dominant theoretical paradigms – primarily collaborative planning and communicative rationality – within the field of urban planning. However, scholars from Human-Computer Interaction have built a theoretical tradition drawing on Activity Theory, among others, to describe computer supported collaborative learning. Collaboration, from this perspective, represents a form of distributed learning situated within a social interaction. Individuals work with each other and technology to converge on shared conceptual understandings of the problem space and to develop a shared praxis for collaboratively addressing those problems. Instead of the tools talking, technology plays a critical role in helping stakeholders develop a common ground for planning and supporting an activity-aware praxis. I use empirical examples from a planning process on Cape Cod, Massachusetts to illustrate these features of Computer Supported Collaborative Learning (CSCL) for a planning audience. I focus, in particular, on how planning support systems mediate group judgments about space and scale to account for spatial scale mismatches between the Cape's watersheds and towns.